Benin : Assessment Letter for Donors. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This letter provides an assessment of recent macroeconomic developments in Benin and an update on the discussions of Fund staff with the Beninese authorities on macroeconomic policies and structural reforms that could form the basis for the authorities' request for a new arrangement supported by the International Monetary Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Benin